Endodontic Sealers with Antibiofilm Properties - A Review - SHREE, M. KAVYA; JAYALAKSHMI; GANESH S, BALAJI; RANI.S, LESLIE (The journal of contemporary issues in business and government, 2020)
Oral bacteria have evolved to form biofilms on hard tooth surfaces and dental materials.Dental materials used in root canal treatment have undergone substantial improvements over the past decade.However,in one place that still has the ability of passage fillings to effectively entomb, kill bacteria, and stop the formation of a biofilm, all of which will prevent reinfection of the root canal system.The most important work of the sealer is to seal the root canal system by removing the remaining bacteria and filling of inaccessible areas of prepared canals.Sealer selection may influence the outcome of endodontic treatment endodontics,root canal sealers is from observations of bases and liners containing the material and their antibacterial and tissue repair abilities.There are three types of endodontic sealers Group 1: Zinc oxide eugenol based sealers, for example, DSI Zoer, Tubli-Seal .Group2 :Calcium Hydroxide based sealers, for example, Sealpex, Group 3: Resin-based sealers, for example, AH26, AH Plus, Diaket,in order to enhance the antimicrobial properties of sealer ,nanoparticle has been incorporated into the sealers. It can reduce the microorganism’s growth in the canal. The aim of this review article is to convey which endodontic sealer has good antibacterial effect and which has least antibacterial effect ,so several articles have been collected and analysed and concluded.